Protective effects of L-arginine on gastric ulcer induced by ethanol in rats: Modulation of oxidative stress - Kaveh Rahimi; Kosar Hassan Pour; Seyedeh Roghayeh Afandak; Fatemeh Razavi; Fatemeh Shojaat Maharlooei (PLoS ONE, 2025)
Gastric ulcers occur due to an imbalance between harmful and protective factors. This study aimed to examine the effect of L-arginine on ethanol-induced gastric ulcers in rats. In this study, 30 male Wistar rats were divided into five groups: a control group that received saline, group 1 which was treated with 70% ethanol to induce gastric ulcers, group 2 that received saline along with L-arginine at a dose of 500 mg/kg administered intraperitoneally, group 3 that was given ethanol along with L-arginine at the same dose but administered orally, and group 4 which received ethanol together with omeprazole at a dose of 10 mg/kg administered intraperitoneally. After the ethanol treatment induced ulceration, gastric lesions were evaluated, and assays were performed to measure antioxidant enzyme levels, malondialdehyde (MDA) levels, and the gene expression of inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS). Treatment with L-arginine or omeprazole reduced ethanol-induced gastric damage by lowering the ulcer index, increasing gastric pH, improving antioxidant status (decreased MDA, increased SOD and CAT), and modulating NO and iNOS levels. L-arginine showed protective effects comparable to those of omeprazole. This study shows that L-arginine can effectively reduce gastric mucosal injury caused by ethanol, achieving results comparable to those of omeprazole. The protective effects of L-arginine are likely due to its ability to enhance antioxidant defenses, regulate gastric acidity, and modulate nitric oxide pathways. These findings highlight the potential therapeutic role of L-arginine in managing gastric ulcers.